2021
DOI: 10.34172/ijhpm.2021.73
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Lenses on the Community Health System: Implications for Policy, Practice and Research

Abstract: Community health systems (CHSs) have historically been approached from multiple perspectives, with different purposes and methodological and disciplinary orientations. The terrain is, on the one hand, vast and diverse. On the other hand, under the banner of universal health coverage (UHC) and the Sustainable Development Goals (SDGs), a streamlined version of 'community health' is increasingly being consolidated in global health and donor communities. With the view to informing debate and practice, this paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Topics such as homosexuality, initiation ceremonies, and contraception conflicted with dominant religions and cultural practices [30,48]. Collective action in the delivery of SRHR services in community health systems can promote ownership, trust and sustainability for the integration of CSE interventions [49][50][51]. It is important for interventions to suit the local context.…”
Section: Discussionmentioning
confidence: 99%
“…Topics such as homosexuality, initiation ceremonies, and contraception conflicted with dominant religions and cultural practices [30,48]. Collective action in the delivery of SRHR services in community health systems can promote ownership, trust and sustainability for the integration of CSE interventions [49][50][51]. It is important for interventions to suit the local context.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these three forms of power, the study identified additional forms or sources of power namely collective action which consists of activities conducted in communal spaces such as schools, churches, health facilities, media platforms, as well as relational power which is about community / family connectedness. Mapping and considering these forms of power ( and in particular the two additional forms of power) when implementing programmes is vital as a community health system “ consists of the set of local actors, relationships, and processes engaged in producing, advocating for, and supporting health in communities and households outside of, but existing in relationship to, formal health structures” ( Schneider & Lehmann, 2016 ; Schneider et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To effectively manage varied power and interests, there is a need to widen participation and promote collective action and accountability ( George et al ., 2018 ; Mulubwa et al ., 2020 ; Schneider et al ., 2022 ; Tetu et al ., 2021 ), in the delivery of VMMC. This study showed that increasing stakeholder engagement in planning, delivering, and monitoring VMMC programmes could be one way of enhancing the delivery, uptake, and sustainability of VMMC.…”
Section: Discussionmentioning
confidence: 99%
“…As policy leaders consider new and effective ways to plan, implement, monitor and evaluate programmes that engage the meaningful participation of diverse groups of citizens, evidence can add clarity to the process and validate the development of comprehensive policies. Policy leadership in health must foster the consolidation of community networks based on social solidarity and two-way trust that can generate analysis, share knowledge, and bring pressure and legitimacy to bottom-up policy-making [25,26].…”
Section: The Change Needed For the Common Goodmentioning
confidence: 99%